The Neuro-Palliative Care for Brain Tumor Patients - the Challenges in Poland: A Review - Mika, Wiktoria; Słowik, Justyna; Sieradzka, Izabela; Wajda, Katarzyna (Journal of Education, Health and Sport, 2025)
Objective: This comprehensive review examines unique clinical, psychosocial policy challenges associated with providing optimal End-of-Life Palliative Care (PC) for patients with malignant brain tumors, focusing specifically on systemic constraints within the Polish healthcare system. Material and Methods: A narrative review and policy analysis was conducted, synthesizing clinical data on neurocognitive function, decision-making capacity, psychosocial outcomes, established international EoL care trends, official health policy documents pertaining to PC eligibility and reimbursement in Poland. Results: Brain tumor patients face a high prevalence of early cognitive impairment (75–80% affected, particularly executive function and memory) and rapid loss of decision-making capacity (DMC), with nearly 90% lacking capacity at EoL. This clinical reality compounds psychosocial burdens, including existential distress (up to 50% reporting anxiety) driven by loss of autonomy and fear of "vanishing away". International trends show improved supportive PC integration (median time to involvement doubled to 126 days) but also persistent aggressive EoL care (increased chemotherapy/ICU use) and significant socioeconomic disparities. In Polish context, access to specialized PC is severely limited by a restrictive reimbursement "basket" based primarily on rigid prognosis criteria (6–12 months survival). Conclusions: The unique and severe clinical complexity of neuro-oncology necessitates early, integrated, and needs-based PC. The reliance on restrictive prognostic criteria in Poland is fundamentally incompatible with rapid decline observed in this patient group, leading to suboptimal EoL care. Urgent policy reform is required to adopt clustered, symptom-based referral criteria to ensure equitable, timely access to specialist PC.